Stability evaluation of fluorescent anti-rabies virus conjugate produced in Instituto Pasteur of São Paulo (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The fluorescent anti-rabies conjugate (FARC) produced in Instituto Pasteur de São Paulo (IP-SP) is obtained by fluorescein isothiocyanate (FITC) conjugation with specific polyclonal antibodies purified and it recommended storage temperature of 4°C protected from light incidence. Given the fundamental importance of this reagent for rabies laboratorial diagnosis, the aim of this study was evaluate its stability in relation to physical factors that can affect the quality and maintenance of product characteristics. To do this, different aliquots of FARC batch IP-TOT1/11 submitted to temperatures of 37, 56, 65 and 80°C for 1hour or exposed to ambient light for 10, 20, 30, 45, 60, 90, 120, 150 minutes and 24 hours were used on direct immunefluorescence (DIF) test on slides with central nervous system imprints of mice infected with Challenge Virus Standard (CVS) and in monolayers of BHK-21 cells infected with Pasteur Virus (PV), with titers previously defined of 1:160 and 1:80, respectively. Also, with one aliquot retained on the recommended conditions, the same tests were performed and exposed for 1, 3, 5, 8 e 10 minutes to ultraviolet (UV) radiation on fluorescence microscopy. The crosses system was adopted to evaluating the fluorescence intensity observed in the reactions, which was attributed 4+ for high fluorescence intensity, 3+ to media intensity, 2+ low intensity and 1+ to total loss of fluorescence. For light exposition, the samples exposed of 10 to 90 minutes received 4+, the samples exposed to 120 and 150 minutes received 3+ and the samples exposed for 24 hours received 2+. The samples submitted to temperatures of 37°C and 56°C received 4+ and the samples submitted to 65 and 80°C showed only traces of residual FITC on the reactions, being impossible observed the characteristics rabies virus citoplasmatic inclusions. And with the increasing of exposition time to UV it was observed the gradual loss of fluorescence intensity reaching to 1+ after 10 minutes. These results showed that FARC tested kept the same quality characteristic even exposed to room light until 90 minutes and 56°C for 1 hour, showing the same florescence intensity of reagent kept on recommended conditions, although it doesn’t be exposed to UV for long periods during the reading of reactions on fluorescence microscopy, showing be a stable reagent and as it has a high value, it must be revaluated when submitted to adverse conditions, avoiding waste.